The impact of subprime crisis on Asia-Pacific Islamic Stock Market - Zhang, H. C.; Hamid, Zarinah (Taylor ans Francis, 2015)
The objective of this study is to examine the impact of the U.S. subprime crisis on the long-term and short-term dynamic relationships between selected Asia-Pacific Islamic stock markets and conventional stock markets in the region. The comovements among these stock markets are examined through cointegration tests, and vector error correction model–based Granger causality tests, for the period from February 2006 to December 2010. The study reveals that, after the debut of the U.S. subprime crisis, Asia-Pacific Islamic stock markets increasingly integrated among themselves and with their conventional counterparts. In addition, the conventional markets of the United States and Japan significantly influence the short-run fluctuations of Asia-Pacific Islamic and conventional markets.